Respuesta :
Answer:
[tex]x = 0.175\cdot (1-\cos 4\cdot \theta)[/tex]
Step-by-step explanation:
Let use the following trigonometric identities:
[tex]\sin^{2}\theta = \frac{1-\cos 2\cdot \theta}{2} \\\cos^{2}\theta = \frac{1+\cos 2\cdot \theta}{2}[/tex]
Then, the equation is simplified by substituting its components:
[tex]x = 1.40\cdot \left(\frac{1-\cos 2\cdot \theta}{2} \right)\cdot \left(\frac{1+\cos 2\cdot \theta}{2} \right)[/tex]
[tex]x = 0.35\cdot (1-\cos^{2}2\cdot \theta)[/tex]
[tex]x = 0.35\cdot \sin^{2}2\cdot \theta[/tex]
[tex]x = 0.35\cdot \left(\frac{1-\cos 4\cdot \theta}{2} \right)[/tex]
[tex]x = 0.175\cdot (1-\cos 4\cdot \theta)[/tex]
Answer:
(1/8) - (1/8)* [cos (4x)]
Step-by-step explanation:
We will apply the corresponding formulas and through algebra we will reach the result in the following steps:
Sin^2 (x) * Cos^2 (x) = {[1 - cos (2x)]/2}*{[1 + cos (2x)]/2}
Sin^2 (x) * Cos^2 (x) =[ 1 - cos^2 (2x)]/4
Sin^2 (x) * Cos^2 (x) = (1/4) - (1/4) * cos^2 (2x)
Sin^2 (x) * Cos^2 (x) = (1/4) - (1/4) * {[1 + cos (2*2x)]/2}
Sin^2 (x) * Cos^2 (x) = (1/4) - (1/8) * [1 + cos (4x)]
Sin^2 (x) * Cos^2 (x) = (1/4) - (1/8) - (1/8)* [cos (4x)]
Sin^2 (x) * Cos^2 (x) = (1/8) - (1/8)* [cos (4x)]